1) x^2 - 11x - 42 = 0
По теореме Виета :
x1+x2= 11 x1= -3
x1*x2= -42 x2= 14
ответ: 14, -3
2)-2x^2 - 5x - 2 = 0 |*-1
2x^2+5x+2= 0
-5+-√25-16
x=
4
-5+-3
x=
4
x= -2
x= -1/2
ответ: -2, -1/2
3)x^4-13x^2 + 36 = 0
Пусть x^2= t, тогда
t^2-13t+ 36= 0
13+-√169-144
t=
2
13+-5
t=
2
t= 9
t= 4
Решим квадратное уравнение, где x^2= t. получим:
x^2= 9 и x^2= 4
х= 3 х= 2
х=-3 х= -2
ответ: 3, -3, 2, -2
ответ: ₁∫²(dx/(√x+1)≈0,452.
Объяснение:
₁∫²(dx/(√x+1)
Сначала решим неопределённый интеграл. ⇒
∫(dx/(√x+1)=∫(1/(√x+1))dx.
Пусть (√x+1)=u ⇒
du=d(√x+1)=(1/(2*√x))dx ⇒
dx=2*√x*du ⇒
∫(1/(√x+1))dx=∫(2*√x/u)du=2*∫(√x/u)du=2*∫((√x+1-1)/u)du=2*∫((u-1)/u)du=
=2*(∫du-∫du/u)=2*u-lnu=2*(√x+1)-2*ln(√x+1)=2*(√x+1-ln(√x+1)).
∫(dx/(√x+1)=2*(√x+1-ln(√x+1)). ⇒
₁∫²(dx/(√x+1)=2*(√x+1-ln(√x+1)) ₁|²=2*((√2+1-ln(√2+1))-(√1+1-ln(√1+1)))
=2*(√2+1-ln(√2+1)-(2-ln(2))=2*(√2+1-ln(√2+1)-2-+ln(2))=
=2*(√2-1-ln(√2+1)+ln(2))≈0,452.
1)x^2 - 11x - 42 = 0
х=14 х=-3
2)-2x^2 - 5x - 2 = 0
D= 25-16=9
x= -0.5 x= -2
3)x^4-13x^2 + 36 = 0
x^2=9 x^2=4
x= -3 x= 3 x=-2 x=2